Navigating the paradox of social development: intersections of technology, exploitation, and sustainable welfare - Baranowski, Mariusz (Przegląd Krytyczny, 2023)
This paper explores the multifaceted concept of social development within economically advanced countries, delving into the implicit assumption of technological advancement as a cornerstone for well-functioning economies. While digital technologies shape broad socio-economic processes, a counterfactual perspective emerges when examining social development through the lens of (nature-based) social welfare. The analysis encompasses the coexistence of advanced technologies with disparities in living standards, resource appropriation mechanisms impacting both populations and environments, and the underexplored negative consequences of techno-economic development. The article addresses the visible and invisible impacts of information technologies, emphasising issues of labour exploitation, resource extraction practices, and the environmental costs of digital production. Critically assessing optimistic scenarios, the paper suggests the need to broaden discussions beyond the positive aspects of technology, considering the challenges for sustainable welfare posed by exploitative labour, resource extraction, and inequitable benefits. The study advocates for an inclusive approach to (nature-based) social welfare, encompassing marginalised issues and proposing concepts such as degrowth as potential solutions to the rapid development of information technologies and their societal implications.